Kepemimpinan paternalistis dan perilaku keselamatan kerja: Kepercayaan terhadap supervisor sebagai mediator - Keifan Adi Prasetyo; Debora Eflina Purba (Fakultas Psikologi Universitas Indonesia dan Ikatan Psikologi Sosial-HIMPSI, 2022)
Occupational safety and health measures must be applied by every industry that has at least 100 workers and industries that have a high risk of danger in their work environment. This research aims to examine the influence of a typical leadership style in Indonesia, namely paternalistic leadership, on the safety behavior of employees in the workplace via trust in the supervisor as the mediator refers to social identity theory. Trust in supervisors is conceptualized as separate dimensions of affective trust and cognitive trust. The data were taken using convenience sampling using online survey research conducted in various Indonesian industrial sectors with a high risk of work accidents (N = 300). Data were analyzed using Hayes’ PROCESS macro ver 3.5.3 on SPSS ver. 26. Results showed that affective trust did not mediate the relationship between paternalistic leadership and safety behavior, but cognitive trust mediated the relationship. Results also showed that affective trust and cognitive trust consecutively mediated the relationship between paternalistic leadership and safety behavior